Assessment of Groundwater Contamination around Bakung Landfill, Lampung, Indonesia Using Geoelectrical Resistivity and Hydrogeochemical Data - Rizka, Rizka; Santoso, Djoko; Warsa, Warsa; Iskandar, Irwan (Journal of Engineering and Technological Sciences, 2026)
This study investigates groundwater contamination caused by leachate migration at the Bakung landfill during the wet and dry seasons using geoelectrical resistivity and hydrogeochemical methods. The objective is to describe groundwater contamination resulting from leachate and assess groundwater quality from nearby wells along the edge of the Bakung landfill. 1D resistivity sounding (vertical electrical sounding (VES)) survey was conducted at eight sounding points using the Schlumberger configuration, and four lines of 2D resistivity imaging (electrical resistivity tomography (ERT)) were acquired inside and outside the landfill site using the Wenner configuration. The 1D resistivity inversion model show that subsurface resistivity values lower than 40 Ωm are likely associated with tuff rocks, whereas resistivity values greater than 40 Ωm are associated with volcanic breccia. The 2D resistivity imaging model indicates a leachate plume. Migrating into the lower layers of the landfill occurs from the northeast and northwest, suggesting potential contamination of shallow groundwater systems as the landfill ages. The hydrogeochemical assessment of groundwater samples followed APHA standards, identifying hydrogeochemical facies using the Piper diagram and interpreting hydrogeochemical processes using the Gibbs and Gaillardet diagrams. The Piper diagram shows the presence of mixed Ca-Mg-Cl, Ca-HCO3, and Na-Cl facies, with the Na-Cl type found only in well W1, which contains leachate. Contaminated areas exhibit slight increases in ionic concentrations. To prevent contamination from migrating into the aquifer, contaminated zones must be identified.